Digitalisasi Layanan Posyandu: Implementasi Sistem Pencatatan Tumbuh Kembang Anak Berbasis WEB di Desa Talagawetan - Sena Kurniawan; Yuni Siti Sarah (Jurnal Medika: Medika, 2026)
Monitoring the growth and development of toddlers at the Posyandu level is highly important as an initial step in preventing severe malnutrition and stunting. However, the operational activities of the Posyandu in Talagawetan Village still completely rely on manual recording systems. This conventional method has various weaknesses, such as being prone to physical data loss or damage, prolonging service queue times, and hindering the monthly reporting recapitulation process to relevant health agencies. This community service activity aims to provide a technological solution by designing and implementing a web-based child growth recording information system, while simultaneously training Posyandu cadres to operate it. The implementation method used is a combination of Diffusion of Science and Technology through the development of the “e-Posyandu” application and direct mentoring Training for the target partners. The service results indicate that the implementation of the e-Posyandu application successfully accelerates the search time for child history data to less than one minute, automates report generation, and secures the toddler medical record database. Furthermore, the existence of an early warning system feature greatly assists cadres in automatically detecting stunting indication trends based on weight curve input. In conclusion, this service digitalization program is proven to be crucial in improving the efficiency of cadres' administrative tasks and ensuring a more measurable quality of toddler health monitoring.